Pelatihan Pembuatan Eco Enzyme Bersama Komunitas Eco Enzyme Lambung Mangkurat Kalimantan Selatan - Dian Masita Dewi (Universitas Lambung Mangkurat, 2021)
Eco enzyme is a multifunctional liquid produced from a 3-month fermentation process with simple ingredients, brown sugar/cane drops, waste or organic waste using a 1:3:10 composition. During this eco enzyme fermentation process, it will produce O3 and O2 gases (ozone and oxygen), this is equivalent to that produced by 10 trees. Some of the benefits of Eco Enzyme are that it can clean polluted rivers, such as antiseptics, fertilize the soil and replace daily household chemical products. The objectives of this community service activity are: 1) to introduce an organic waste management program into eco-enzyme. 2) this community service activity will be published in a national journal. This activity will be held from February 21 to May 26, 2021. The target audience involved in this activity is 10 members of the Lambung Mangkurat Eco Enzyme Community Kalimantan. Selection of target audience based on the closest distance. The methods used in the implementation of this activity are lectures, simulations and practices of processing organic waste into environmentally friendly eco enzymes. The conclusion of the program is that all participants are enthusiastic and can produce good quality eco enzymes. Based on the evaluation results indicate that the satisfaction of the participants is very high when viewed from all aspects of the assessment.